SPIDERS (ARACHNIDA: ARANEI) OF FIVE FOREST HABITATS OF THE POLISSYA NATURE RESERVE (ZHYTOMYR AREA, UKRAINE) - Evtushenko, K. V.; Kobzar, L. I. (Видавництво НДУ ім. М. Гоголя, 2023)
The Polissya Nature Reserve is located in the zone of mixed forests in the physical geographic region of Zhytomyr Polissya (Zhytomyr region, Ukraine). The first data on the spiders of the reserve were obtained by Guryanova V. She gave a list of 66 species from five forest and one swamp coenoses of the Perga forestry. Later, K. Evtushenko and L. Kobzar in an abstract reported on the discovery of 51 species from 14 families from five forest coenoses of the Selezivka Forestry. The list of spiders of the reserve was supplemented by 21 species. Currently, a list of all detected species and their coenotic distribution is provided. The data were obtained on the material collected by the method of soil traps in a pine lichen forest, pine green moss forest, pine-birch blueberry forest, pine-birch molinia forest and birch-oak-elm forest. The material consisted of 866 adult specimens of spiders. Most of the detected species live on the surface of the soil or in the litter. These are common forest species that prefer moist and shaded conditions. Only a few species are rare for Ukrainian Polissya: Arctosa lutetiana (Simon, 1876) (known from the Shatsk National Nature Park), Mustelicosa dimidiata (Thorell, 1875) (recorded in the v. Kozyn near Kyiv) and Zora sp. 1 and Zora sp. 2 – not identified to species close to Z. manicata Simon, 1878. The total list of spiders of the Polissya Nature Reserve consisted of 87 species from 17 families. Infection of spiders of the Liocranidae family with larvae of the fly Ogcodes sp. (Diptera: Acroceridae) was recorded for the first time. Two females of the spider Agroeca proxima (O. P.-Cambridge, 1871) were infected. Females were collected in pine lichen forest and birch-oak-elm forest. Larvae are localized inside the abdomen of spiders near the epigastric slit. The article contains photos of the location of the fly larvae inside the spider and the appearance of the larvae.
ПАВУКИ (ARACHNIDA: ARANEI) П’ЯТИ ЛІСОВИХ БІОТОПІВ ПОЛІСЬКОГО ПРИРОДНОГО ЗАПОВІДНИКА (ЖИТОМИРСЬКА ОБЛАСТЬ, УКРАЇНА)
Поліський природний заповідник розташований в зоні мішаних лісів у фізико географічній області Житомирське Полісся (Житомирська область, Україна). Перші дані про павуків заповідника були отримані В. Гур’яновою. Вона навела список 66 видів з п’яти лісових і одного болотного ценозів Перганського лісництва. Пізніше К. Євтушенко та Л. Кобзар повідомили про виявлення 51 виду з 14 родин в п’яти лісових ценозах Селезівського лісництва. Список павуків заповідника був поповнений 21 видом. Наразі надається список всіх виявлених видів та їх ценотичний розподіл. Дані були отримані на матеріалі, зібраному методом ґрунтових пасток у сосновому лісі лишайниковому, сосновому лісі зеленомоховому, сосново-березовому чорничному лісі, сосново-березовому молінієвому лісі та березово-дубово-в’язовому лісі. Матеріал становив 866 статевозрілих екземплярів павуків. Більшість виявлених видів мешкають на поверхні ґрунту або в підстилці. Це звичайні лісові види, які віддають перевагу вологим і затіненим умовам. Лише кілька видів є рідкісні для українського Полісся: Arctosa lutetiana (Simon, 1876) (відомий з Шацького національного природного парку, Mustelicosa dimidiata (Thorell, 1875) (відмічений в с. Козин біля Києва) та Zora sp. 1 і Zora sp. 2., які вірогідно представники одного виду, близького до Z. manicata Simon, 1878. Загальний список павуків Поліського природного заповідника склав 87 видів з 17 родин. Вперше було зафіксовано зараження павуків родини Liocranidae личинками мухи Ogcodes sp. (Diptera: Acroceridae). Зараженими були дві самиці павука Agroeca proxima (O. P.-Cambridge, 1871). Самиці були зібрані в сосновому лісі лишайниковому та березово-дубово-в’язовому лісі. Личинки локалі зовані всередині черевця павуків біля епігастральної щілини. В статті наведені фотографії розташування личинок мухи всередині павука та зовнішнього вигляду личинок.
Keywords: spiders; Polissya Nature Reserve; Ukraine